Gender Differences in the Association Between Screen Time and Depression - Lauren E. Kleidermacher, MSc; Mark Olfson, MD, MPH (Elsevier, 2024)
Introduction: Previous research has shown that screen time is associated with depression, especially in children. Some evidence further suggests that the association may be stronger in women than in men, although findings are inconclusive. This cross-sectional study examines the association between screen time and depression in representative U.S. adults, stratified by gender. Methods: This study used data from the 2015-2016 National Health and Nutrition Examination Survey; analysis was conducted in 2023. Screen time was partitioned into 3 categories-0-2 hours, 3-4 hours, and >4 hours-and included TV and computer time. Depression was defined as a Patient Health Questionnaire score ≥10. TV time and computer time were also analyzed as separate exposures. A multivariable logistic regression model examined the association between screen time and depression. Results: Results showed that there was a significant interaction between gender and screen time. An association between the highest screen time exposure group and depression was observed for women (>4 hours per day: OR=3.09; 95% CI=1.68, 5.70). The type of screen time affected the relationship, with TV showing a stronger association than computer time. There were no significant associations in men across all exposure groups. Conclusions: Further research is needed to determine whether higher levels of screen time, especially TV, may be a depression risk marker for women but not men.